Whey protein polymerisation and its applications in environmentally safe adhesives. (14th July 2016) - Guo, Mingruo; Wang, Guorong
Abstract : Whey protein is a group of globular proteins from cheese whey. It is a safe, degradable, renewable and abundant natural material compared with synthetic polymers. Native whey proteins do not exhibit good adhesive properties due to their low molecular weights and compact globular structures; however, under thermal treatment, these globular structures can be unfolded to form polymers or aggregates through intermolecular disulphide bonds via a thiol–disulphide interchange. Heat‐induced whey protein polymer exhibits good adhesive properties. With the addition of a cross‐linker, stabiliser or co‐binder, different types of wood and paper adhesives can be formulated using polymerised whey protein.